A taxonomic revision of Amorphophallus Blume ex Decne. Sect. Conophallus (Schott) Engl. (Araceae) in India - Jaleel, V. Abdul; Sivadasan, M.; Alfarhan, Ahmed H.; Thomas, Jacob; Alatar, A. A. (Bangladesh Journal of Plant Taxonomy, 2012)
The diagnostic characters of Amorphophallus Blume ex Decne. sect. Conophallus (Schott) Engl. is amended based on detailed studies of characteristics of the constituent species. In India the section is represented by six species, viz. A. bognerianus Sivad. et Jaleel, A. bulbifer (Sims) Blume, A. carnosus Engl., A. commutatus (Schott) Engl., A. nicolsonianus Sivad. and A. oncophyllus Prain ex Hook. f. The species A. commutatus forms a complex with three varieties, viz. var. commutatus, var. anmodensis Sivad. et Jaleel, and var. wayanadensis Sivad. et Jaleel. Keys to the species and varieties have been provided to facilitate easy identification. Amorphophallus carnosus has been rediscovered after more than 100 years of its first discovery and collection. Amorphophallus bulbifer has comparatively wider distribution in India with extended distribution in Bangladesh and Myanmar. The species A. bognerianus, A. carnosus, A. commutatus, A. nicolsonianus and A. oncophyllus are exclusive endemics of India. DOI: http://dx.doi.org/10.3329/bjpt.v19i2.13127 Bangladesh J. Plant Taxon. 19(2): 135-153, 2012 (December)